Perencanaan Knowledge Management System Untuk Tata Kelola Perguruan Tinggi - Supit Mamuaya; Harisno Harisno; Mihuandayani Mihuandayani; Rillya Arundaa (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2020)
Abstract— A variety of knowledge, especially for universities in making standards, is one of the important things to be managed and documented. The standard drafting process is carried out by the drafting team in holding meetings and meetings directly. Constraints arise when in the drafting process, the drafting team is difficult to determine the time of meeting the standard discussion directly due to busyness and work constraints. In addition, the unavailability of online media repositories for the PPEPP process is another obstacle because the standard documents that have been discussed are only printed and stored as campus files. This storage process is vulnerable to damage, loss, and sometimes it is difficult to do a search if it is merged with other documents. STMIK Multicom management system is not yet available that can accommodate these knowledge. Thus, to ensure the flexibility and changes of STMIK Multicom to keep up with technological developments, a system that can accommodate individual and organizational knowledge in one portal is needed so that the sharing process becomes easier. Through a systematic Knowledge Management System application development plan, the results of system testing conducted on respondents as system users obtained results of 81.16% as the value of benefits for the evaluation of KMS application planning.